The explosive power of couple arms and their own relationship to the performance of the smashed beating in badminton for young people (17-19 years( - Nabhan, Nada (Journal of Physical Education, 2016)
This thesis includes five chapters: first chapter is talking about the introduction and The importance of the research which is concentrated in studying the certain kinds of muscle strength for the couple arms and their own relationship to the performance of the basic skills in badminton for the young , and then the problem of thesis , there targets , hypothesis and the field of thesis. In the second chapter the researchers choose some subjects like (basic skills, smashed beating, technical steps for smashed beating and strength in badminton). The Similar Studies: The Research of Mr. Mohamme Jassim al-Khalidi was chosen. The third chapter has included of The Research Methodology and the field procedures, the user community , the research sample , means of data collection instruments , the tools that are used and depended in the research , the action of the research , the field experience , exploratory tests as well as the statistical methods. The Fourth chapter has included Submitting and displaying the results, analyzing and discussing them. The fifth chapter has included Conclusions and recommendations